2018
DOI: 10.1080/15459624.2018.1424339
|View full text |Cite
|
Sign up to set email alerts
|

Physical chemical properties and cell toxicity of sanding copper-treated lumber

Abstract: To protect against decay and fungal invasion into the wood, the micronized copper, copper carbonate particles, has been applied in the wood treatment in recent years; however, there is little information on the health risk associated with sanding micronized copper-treated lumber. In this study, wood dust from the sanding of micronized copper azole-treated lumber (MCA) was compared to sanding dust from solubilized copper azole-treated wood (CA-C) and untreated yellow pine (UYP). The test found that sanding MCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The detailed testing procedures and the diagram of the laboratory testing system can be found in recent studies. [20][21][22] In addition, baseline tests were performed when the saw/sander was running but not sawing/sanding any wood to measure the emission from the machines.…”
Section: Aerosol Samplesmentioning
confidence: 99%
“…The detailed testing procedures and the diagram of the laboratory testing system can be found in recent studies. [20][21][22] In addition, baseline tests were performed when the saw/sander was running but not sawing/sanding any wood to measure the emission from the machines.…”
Section: Aerosol Samplesmentioning
confidence: 99%
“…There is a growing concern over the potential exposure of workers to the micronized/nanoscale copper particles released during the handling and mechanical processing of copper-treated lumber. A recent toxicity study indicated that sanding of copper-treated lumber can produce nanoscale copper particles that are potentially cytotoxic [6]. However, the potential toxicity of metal nanoparticles is greatly affected by their chemical states, aspect ratios, and degree of agglomeration.…”
mentioning
confidence: 99%